AB0848 Canakinumab Pre-Filled Syringe VS Triamcinolone Acetonide in the Treatment of Acute Gouty Arthritis Attacks: Results from A Post-Hoc Analysis in Difficult-To-Treat Patients. (10th June 2014) - Sunkureddi, P.; Toth, E.; Brown, J.; Kivitz, A.; Stancati, A.; Richard, D.; Lheritier, K.; Möricke, R.
Abstract : Background: Canakinumab (CAN), a selective, fully human anti-IL-1β monoclonal antibody, is the only approved biologic in the European Union for the symptomatic treatment of adult patients (pts) with difficult-to-treat gouty arthritis (GA). A liquid formulation, presented as pre-filled syringe (CAN-PFS) has been developed to improve upon the lyophilized form (CAN-LYO) that requires reconstitution. Here, we report results from a post-hoc analysis of the 12-week data of a Phase III trial. Objectives: To evaluate the efficacy and safety of CAN-PFS vs triamcinolone acetonide (TA) in a subset of difficult-to-treat GA pts defined as a) unable to use NSAIDs and colchicine due to contraindication, intolerance or lack of efficacy, and b) currently on urate-lowering therapy (ULT), or previously failed ULT or in whom ULT is otherwise contraindicated. Methods: This was a 12-week, multicenter, double-blind, active controlled study. The design and methodology of the study have been reported earlier 1 . The primary efficacy measure was overall pain intensity in the most affected joint measured on VAS scale (0-100 mm) at 72 h post-dose. Secondary endpoints included time to first new attack and safety over 12 weeks. Results: Of the 397 GA pts randomized, 106 (CAN-PFS, n=34; CAN-LYO, n=43; TA, n=29) met the subgroup definition. CAN-PFS provided a statistically significant reduction in pain intensity at 72 h post dose vs TA (estimated difference, -30.7mm; 95%CI: -42.1, -19.3, p≤0.05). The least square mean pain scores at 72 h post-dose for CAN -PFS and LYO, were14.7mm and 19.3mm, respectively; both lower than that for TA (45.4mm). CAN-PFS treatment significantly delayed time to first new attack vs TA with a relative risk reduction of 92% (HR, 0.08; 95%CI: 0.01, 0.63, p≤0.05) over 12 weeks. Adverse events (AEs) were reported in 12 (35.3%), 16 (37.2%) and 14 (48.3%) pts in CAN-PFS, CAN-LYO and TA groups, respectively. Serious AEs were reported in 7 pts [CAN-PFS, n=1 (2.9%); CAN-LYO, n=5 (11.6%); TA, n=1 (3.4%)], with infections [CAN-PFS, n=1 (2.9%); CAN-LYO, n=2 (4.7%); TA, n=0)] being the most common SAEs. One patient in the CAN-LYO group had serious aortitis, which was coded under vascular disorders system organ class, but adjudicated as an opportunistic infection by the independent adjudication committee. No deaths were reported during the study. Conclusions: This analysis provides evidence for the efficacy of CAN in difficult-to-treat GA pts either in pre-filled syringe or lyophilized formulation compared to a potent long acting systemic corticosteroid. CAN-PFS provided better pain relief and reduced the risk of new attacks compared to TA. The safety profile in this population was consistent with that of the overall study population and with that known from previous studies. References: Sunkureddi et al. Arthirits & Rheum 2013; 65. Disclosure of Interest: P. Sunkureddi Consultant for: Novartis, Bristol Myers Squibb, Speakers bureau: Pfizer, Takeda, Bristol Myers Squibb, UCB, Amgen, Abbott, Shinogi, Savient, E. Toth: None declared, J. Brown Grant/research support: Amgen, Bristol Myers Squibb, Eli Lilly, Novartis, Merck, Pfizer, Roche, Servier, Sanofi-aventis, Takeda, Warner Chilcott, Consultant for: Amgen, Eli Lilly, Merck, Warner Chilcott, Sanofi-aventis, Speakers bureau: Amgen, Eli Lilly, Novartis, Merck, A. Kivitz Grant/research support: Novartis, A. Stancati Shareholder of: novartis, Employee of: novartis, D. Richard Shareholder of: Novartis, Employee of: Novartis, K. Lheritier Shareholder of: Novartis, Employee of: Novartis, R. Möricke: None declared DOI: 10.1136/annrheumdis-2014-eular.1846